Electromagnetic shielding of a building: |modelling and measurement - Karacagil, Piraye. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Sciences and Engineering, 1997., 1997)
In this thesis, shielding effectiveness of a building is calculated by using a multilayer model and compared with the results of the measurements taken inside a building. The computer program used for this objective has been constructed to simulate the importance of the multilayer structures. For the same and different floors in a building, shielding effectiveness values are calculated and compared with the experimental results. Measured values are obtained by using an automated meaSuring system developed for this study. Furthermore, the shielding effectiveness measurements of the shielded enclosures (Gigahertz Transverse Electromagnetic (GTEM) and Compact Diagnostis Chamber (CD)) in accordance with the MIL-STD 285 and IEEE 299 are also carried out as another experimental study of this thesis. All results obtained for different frequency ranges and at different places are presented with several graphics.
Keywords: Shielding (Electricity); Magnetic shielding.